Guided vs. conventional anti-platelet therapy for patients with acute coronary syndrome: A meta-analysis of randomized controlled trials - Zhong, Peng-Yu; Deng, Jian-Ping; Zhao, Jing-Hong; Peng, Lei; Liu, Tao; Wang, Hao-Yu (Frontiers in Cardiovascular Medicine, 2023)
Background Whether guided antiplatelet therapy in patients with acute coronary syndrome (ACS) is effective in improving net clinical benefits compared with conventional antiplatelet therapy remains controversial. Therefore, we assessed the safety and efficacy of guided antiplatelet therapy in patients with ACS and undergoing percutaneous coronary intervention. Method We searched PubMed, EMBASE, and Cochrane Library databases to select the relevant randomized controlled trials comparing the guided and conventional antiplatelet therapy in patients with ACS. The primary and safety outcomes are major adverse cardiovascular events (MACE) and major bleeding, respectively. The efficacy outcomes included myocardial infarction, stent thrombosis, all-cause death, and cardiovascular death. We selected the relative risk (RR) and 95% confidence intervals (CIs) as effect size and calculated it using the Review Manager software. In addition, we evaluated the final results by trial sequential analysis (registered by PROSPERO, CRD 42020210912). Results We selected seven randomized controlled trials and included 8,451 patients in this meta-analysis. Guided antiplatelet therapy can significantly reduce the risk of MACE (RR 0.64, 95% CI 0.54–0.76, P < 0.00001), myocardial infarction (RR 0.62, 95% CI 0.49–0.79, P = 0.0001), all-cause death (RR 0.61, 95% CI 0.44–0.85, P = 0.003), and cardiovascular death (RR 0.66, 0.49–0.90, P = 0.009). In addition, there is no significant difference between the two groups in stent thrombosis (RR 0.67, 95% CI 0.44–1.03, P = 0.07) and major bleeding (RR 0.86, 95% CI 0.65–1.13, P = 0.27). The subgroup analysis showed that the guided group based on genotype tests could bring benefits in MACE and myocardial infarction. Conclusions The guided antiplatelet therapy is not only associated with a comparable risk of bleeding but also with a lower risk of MACE, myocardial infarction, all-cause death, cardiovascular death, and stent thrombosis than the conventional strategy in patients with ACS.